Inflammatory Myofibroblastic Tumor of the Breast: A Case Report - Karaoglu, Ahmet Salih; Demir, Mahmut Hudai; Ayaz, Abdullah; Uysal, Hamza; Soylemez, Tuce; Eren, Tunc; Aydin, Abdullah; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2020)
Inflammatory myofibroblastic tumors (IMTs) of the breast are extremely uncommon lesions, usually labelled as a subgroup of inflammatory pseudotumors. They are composed of inflammatory cells and bland spindle cells without nuclear atypia. Nearly half of all IMTs of the breast include clonal translocation of the anaplastic lymphoma kinase (ALK) gene, located at the chromosome band 2p23, and generally present with a palpable lump, swelling, and pain. Herein, we present a 66-year-old female patient with pain, swelling and a palpable lump in her right breast. A 40×26 mm sized T1A hypointense and T2A hyperintense mass with slightly lobulated margins was detected at breast magnetic resonance imaging. A mass associated with an intramammary lymph node was evaluated in the upper inner quadrant of the right breast via mammography. The results were considered as BI-RADS 3. Breast-conserving surgery with sentinel lymph node biopsy was performed. During pathological evaluation, cytoplasm with poorly-defined margins, and large-nucleoli tumor cells with benign ducts between these tumor cells, were observed. Intensive inflammatory cell infiltration and sclerotic changes in different areas were also noted. The lesion stained positive for caldesmon, smooth muscle actin, vimentin, CD10, and S100; however, it was negative for ALK on immunohistochemistry. The patient remained disease-free after the surgical procedure. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 305-308